Relationship Marketing: A Source of Competitive Advantage - Sehgal, N. K. (Indian Journal of Marketing, 2007)
The single most important thing to remember about any enterprise is that there are no results inside its walls. The result of a business is a satisfied customer." In present era of cut-throat competition, it is no longer enough to satisfy the customers. You must delight them! As Philip Kotler puts it, "Today you have to run faster to stay in the same place." The most important tool available to the business firms these days to make the customers happy is "Relationship Marketing".